Formation Of Tio2 Nanotubular Structure In Fluorinated Ethylene Glycol Electrolytes Containing Additives By Anodisation - Taib, Mustaffa Ali Azhar (2018)
TiO2 nanotube arrays (TNTs) have attracted significant interest as the most promising candidate for photo-induced reaction applications. The electrolyte composition is the one of critical factor for oxide formation by anodisation. The TNTs were fabricated in ethylene glycol (EG)/ ammonium fluoride (NH4F) electrolyte containing various additives (H2O, H2O2, KOH, LiOH and Na2CO3) as O2- and/or OH- providers. The properties including morphology, structural of formed oxide and crystallinity were investigated. The TNTs formed in EG/NH4F/H2O2 resulted in grassy structure (wall thickness ~ 10 nm) owing to high chemical etching at the tip of nanotubes. The TNTs formed in EG/NH4F/KOH electrolyte was partially crystalline with average tubes length 6.1 μm. The OH- ions suppress the excessive surface etching at the tips of nanotubes. Meanwhile, the addition of Na2CO3 in EG/NH4F electrolyte was successfully formed as-anodised free standing TNTs (FSTNTs) due to gas evolution which aids in weakening the adherence of anodic film on Ti. The as-anodised FSTNTs contain nanocrystallite anatase. The grassy TNTs demonstrated the highest photocatalytic decolouration efficiency of MO (91.7%) after 2 h owing to the capability of anatase phase to retain at 600 oC at the tip of grassy structure.